O OPTIMALISASI PENGGUNAAN MEDIA PEMBELAJARAN DENGAN GOOGLE WORKSPACE FOR EDUCATION, WHATSAPP DAN KUIS INTERAKTIF PADA MATA PELAJARAN BAHASA BALI DI SMA NEGERI 3 AMLAPURA - Adi Upadana, I Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Digital era learning requires teachers to provide interesting, innovative and creative teaching and learning materials that are easy to access, so that students are not bored and can absorb the material provided well. Learning media that is quite easy to use and access is the google workspace for education application which is an application produced by the Ministry of Education, Culture and Research in collaboration with Google to help realize education in the digital era. The Whatsapp application can also be used to provide learning content, as well as interactive quizzes to help generate student motivation. Overall, the results of the application of optimizing the use of learning media with google workspace for education, whatsapp and interactive quizzes in Balinese language subjects at Senior High School 3 Amlapura get a good average and easy to access material.